M/G/oo queue systems in the pandemic period study - Ferreira, M. A. M. (Applied Mathematical Sciences, 2014)
Even after the Humanity efforts and great success in infectious diseases control, still epidemics happen, being the annual influenza outbreaks examples of those occurrences. To forecast the epidemic period length is very important because, in this period, it is necessary to strengthen the health care, demanding extra availability in human and material resources, with a huge increase of expenses. More pertinently, this happens with the pandemic period, since a pandemic is an epidemic with a great population and geographical dissemination. Predominantly using results on the M|G|? queue busy period, it is presented an application of this queue system to the pandemic period’s parameters and distribution function study. The choice of the M|G|? queue for this model is quite adequate since the greatest is the number of contagions the greatest the possibility that they occur according to a Poisson process.